2010
DOI: 10.1093/ntr/ntq156
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Depressive Symptom Interactions on Adolescent Smoking Prevention Program Mediators: A Mediated Moderation Analysis

Abstract: Introduction: Smoking prevention interventions have been shown to be effective in reducing smoking prevalence in the United States. Further work is needed to address smoking in China, where over one third of the world's current smokers reside. China, with more than 60% of the male population being smokers, also presents a unique opportunity to test cognitive processes involved in depression, social influences, and smoking. Adolescents at-risk for developing depression may process social information differently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Susceptibility to peer influences may vary by gender, race, and age (7). Several studies have found that depressed adolescents are more susceptible to social factors associated with smoking, namely with perceived prevalence of smokers and pro-smoking normative beliefs (8).…”
Section: Introductionmentioning
confidence: 99%
“…Susceptibility to peer influences may vary by gender, race, and age (7). Several studies have found that depressed adolescents are more susceptible to social factors associated with smoking, namely with perceived prevalence of smokers and pro-smoking normative beliefs (8).…”
Section: Introductionmentioning
confidence: 99%
“…Those analyses were adjusted for best friends’ smoking and for perceived smoking norms, making it unclear whether the program affected those proximal outcomes. A study of seventh-graders in China found program effects on recent smoking [18] and on affiliation with smoking friends [19] only among boys who were both highly depressed and already smokers. That study used a self-report measure of friends’ smoking, so the authors could not determine whether the program changed perceptions, actual friend affiliations, or both [19].…”
mentioning
confidence: 99%
“…With regard to peer influences, recent studies indicate that friends’ disruptive behaviors (van Lier, Huizink, & Vuijk, 2011), normative beliefs about peers’ frequency of substance use (Ringwalt et al, 2009), peer aggression (DeGarmo et al, 2009), and perception of friends’ use (Sakuma, Sun, Unger, & Johnson, 2010) were mediators of program effects. Changes in perceived friends’ encouragement to use and in friends’ consumption behavior also mediated program effects on growth in substance use during adolescence (Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%